Antibacterial activity, osteogenic and angiogenic behaviors of copper-bearing titanium synthesized by PIII&D. Issue 7 (25th January 2016) - Yu, Le; Jin, Guodong; Ouyang, Liping; Wang, Donghui; Qiao, Yuqin; Liu, Xuanyong
Abstract : Two types of Cu-bearing specimens with or without nanoparticles on Ti surface synthesized by PIII&D showed disparate biological responses. Abstract : Cu-bearing biomaterials have drawn considerable interest in hard tissue replacement. However, a better compromise between the biocompatibility and cytotoxicity of incorporated copper is still required. In this work, two types of Cu-bearing surfaces were obtained on Ti by altering the processing parameters during PIII&D. One with a certain amount of copper in metallic form on the Ti surface shows enhanced antibacterial ability, osteogenic and angiogenic capabilities, whereas unfavorable biocompatibility is observed from the other Ti surface in the presence of Cu-bearing nanoparticles. Disparate biological differences between two types of Cu-bearing Ti surfaces synthesized by the same single technique provides insights for better understanding of the underlying mechanism between the positive and negative bioeffects of Cu-bearing biomaterials.